Chest Radiology Tutorial (Out of Print) - Eric Bensadoun; Tom Dolan (Association of American Medical Colleges, 2007)
Abstract This is an interactive tutorial that serves as an introduction to chest x-ray interpretation for medical students and residents. This teaching tool can be used by students on their own, or by the teacher to supplement other material. In addition to text and pictures, this tutorial contains interactive features which supplement the text and make it a more dynamic learning experience. The first part of the tutorial focuses on the normal chest radiograph anatomy while the second part consists of ten cases representing some of the most common patterns of abnormalities seen on a chest x-ray. The second part of the tutorial uses an interactive question and answer process that guides the student through a stepwise approach to chest x-ray interpretation, which includes recognition of the abnormality, pattern description, and finally the differential diagnosis of the abnormality. Currently this resource is part of the curriculum for the third-year medicinal students during their medical clerkship rotation. At our institution, students review the tutorial on their own at the start of the clerkship and then they have a lecture on pulmonary medicine where chest x-rays cases are reviewed. This tutorial gives students a firm grounding in the basics of chest x-ray interpretation which they can build on during the rest of their clerkships.